2022
DOI: 10.3389/fmicb.2022.1004495
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community and fermentation characteristic of whole-crop wheat silage treated by lactic acid bacteria and Artemisia argyi during ensiling and aerobic exposure

Abstract: Whole-crop wheat silage (WCWS) is an excellent feed material for ruminants. However, microbial fermentation during silage production consumes valuable nutrients, decreasing the quality of silage. The main objective of this study was to assess how the addition of increasing amounts of Artemisia argyi (AA) affected fermentation quality, microbial composition, and mycotoxin production in whole-crop wheat at dough stage (WCWD) silage during ensiling to aerobic exposure compared with Lactiplantibacillus buchneri (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 64 publications
4
9
0
Order By: Relevance
“…However, in this study, for all groups, the richness and diversity of fungal community decreased in the middle and later stages of aerobic exposure. A similar result was found by Wang et al. (2022) , who reported that after 12 days of aerobic exposure, the richness and diversity of fungal community decreased in whole-crop wheat silage.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, in this study, for all groups, the richness and diversity of fungal community decreased in the middle and later stages of aerobic exposure. A similar result was found by Wang et al. (2022) , who reported that after 12 days of aerobic exposure, the richness and diversity of fungal community decreased in whole-crop wheat silage.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, in this study, the BL, BM, BH, and CL groups shifted from Proteobacteria to Firmicutes during early aerobic exposure, the BL and BH groups shifted from Proteobacteria to Firmicutes during the middle period of aerobic exposure, the CM and BH groups shifted from Proteobacteria to Firmicutes during the later period of aerobic exposure, and the CH group shifted from Proteobacteria to Firmicutes throughout the period of aerobic exposure. Similar results were also found in natural sugarcane tops silage, whole-crop wheat silage, and alfalfa silage after 3, 12, and 20 days aerobic exposure, respectively ( McGarvey et al., 2013 ; Zhang et al., 2019 ; Wang et al., 2022 ). These results suggest that there are particular environmental conditions for the proliferation of Firmicutes, such as sufficient organic acids and lower pH ( Hou et al., 2022 ).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The results of this research revealed that the aerobic stability was lower in the HO treatment than that in other treatments, suggesting that the higher percentage of oats was unfavorable for the storage of FTMR after aerobic exposure, following a previous trial that the oat could reduce the aerobic stability [30], which may be due to the lower AA content in the HO treatment before aerobic exposure was insufficient to limit the proliferation of fungi, especially yeast [31]. Moreover, Pitt et al [32] and Salawu [33] reported that the higher buffering capacity and secondary plant metabolites (e.g., saponins) in legumes could inhibit the growth of spoilage microorganisms.…”
Section: Discussionmentioning
confidence: 65%
“…This did not occur in the group with the addition of the strain Q1-2, and the treatment group was almost free of Aspergillus at the end of fermentation, suggesting that the strain Q1-2 not only reduces mycotoxins but also effectively inhibits fungal growth. In the practical applications of feeds, where aerobic exposure is often required, treatment groups with the fungi inhibiting effects of LAB may have better feed quality in actual production [ 43 ]. In fact, the inhibition of the growth of associated fungi is not a sufficient condition for a reduction in mycotoxin content.…”
Section: Discussionmentioning
confidence: 99%